Developing A Surgical Rationale of Bile Culture and Sensitivity to Guide Targeted Antibiotics in Laparoscopic Cholecystectomy in a Tertiary Care Hospital in Nepal - Dahal, Romi; Acharya, Lokesh; Regmee, Sujan; Maharjan, Prabir; Sharma, Pooja (Journal of Institute of Medicine Nepal, 2025)
Introduction Laparoscopic cholecystectomy is the standard surgical treatment for benign gallbladder conditions. Traditionally, antibiotics have been used empirically in patients to lower the risk of post operative complications. Earlier routine use of antibiotic has now been replaced with single dose preoperative antibiotic. But, the emergence of anti-microbial resistant organisms has raised concerns regarding the use of broad spectrum antibiotics including ceftriaxone to all cases. Methods This is a single-centered, prospective study. Data collection was done between January 2025 to April 2025. There were 148 patients included in the study. Single dose ceftriaxone was given at induction. Bile was collected during the intraoperative period and culture was sent. Association of bile C/S with various preoperative and postoperative factors were analyzed. Results In our study, bile culture was positive in 11 of 148 patients (7.4%). Escherichia coli and klebsiella pneumoniae were the predominant isolates (72%). No significant association of the bile culture colonization was observed with either age, gender or BMI. Those who were immunocompromised had higher bile culture microbial growth rates (21.1% vs. 5.4 %; p = 0.036). Signficantly higher culture growth rates were also noted in infective cases (29.4%). Among the cases that had growth on bile culture, 100% of the organisms were resistant to the routinely used prophylactic antibiotic. Conclusion Routine bile culture positivity in laparoscopic cholecystectomy is low in our study when prophylactic ceftriaxone was given. While additional prophylactic antibiotics may not be universally required, selective use of antibiotic other than ceftriaxone is justified in high-risk groups such as diabetic patients or those with infective pathology.